Interventions in Nicotinamide Adenine Dinucleotide Metabolism, the Intestinal Microbiota and Microcin Peptide Antimicrobials - Baquero, Fernando; del Campo, Rosa; Martínez, José-Luis (Frontiers in Molecular Biosciences, 2022)
A proper NADH/NAD+ balance allows for the flow of metabolic and catabolic activities determining cellular growth. In Escherichia coli, more than 80 NAD+ dependent enzymes are involved in all major metabolic pathways, including the post-transcriptional build-up of thiazole and oxazole rings from small linear peptides, which is a critical step for the antibiotic activity of some microcins. In recent years, NAD metabolism boosting drugs have been explored, mostly precursors of NAD+ synthesis in human cells, with beneficial effects on the aging process and in preventing oncological and neurological diseases. These compounds also enhance NAD+ metabolism in the human microbiota, which contributes to these beneficial effects. On the other hand, inhibition of NAD+ metabolism has been proposed as a therapeutic approach to reduce the growth and propagation of tumor cells and mitigating inflammatory bowel diseases; in this case, the activity of the microbiota might mitigate therapeutic efficacy. Antibiotics, which reduce the effect of microbiota, should synergize with NAD+ metabolism inhibitors, but these drugs might increase the proportion of antibiotic persistent populations. Conversely, antibiotics might have a stronger killing effect on bacteria with active NAD+ production and reduce the cooperation of NAD+ producing bacteria with tumoral cells. The use of NADH/NAD+ modulators should take into consideration the use of antibiotics and the population structure of the microbiota.